The Involvement of TRPC3 channels in Sinoatrial Arrhythmias - Yue-Kun eJu; Bon Hyang Lee; Sofie eTrajanovska; Guoliang eHao; David G Allen; Ming eLei; Mark B Cannell (Frontiers in Physiology, 2015)
Atrial fibrillation (AF) is a significant contributor to cardiovascular morbidity and mortality. The currently available treatments are limited and AF continues to be a major clinical challenge. Clinical studies have shown that AF is frequently associated with dysfunction in the sino-atrial node (SAN). The association between AF and SAN dysfunction is probably related to the communication between the SAN and the surrounding atrial cells that form the SAN-atrial pacemaker complex and/or pathological processes that affect both the SAN and atrial simultaneously. Recent evidence suggests that Ca2+ entry through TRPC3 (Transient Receptor Potential Canonical-3) channels may underlie several pathophysiological conditions -including cardiac arrhythmias. However, it is still not known if atrial and sinoatrial node cells are also involved. In this article we will first briefly review TRPC3 and IP3R signalling that relate to store/receptor-operated Ca2+ entry (SOCE/ROCE) mechanisms and cardiac arrhythmias. We will then present some of our recent research progress in this field. Our experiments results suggest that pacing-induced AF in angiotensin II (Ang II) treated mice are significantly reduced in mice lacking the TRPC3 gene (TRPC3-/- mice) compared to wild type controls. We also show that pacemaker cells express TRPC3 and several other molecular components related to SOCE/ROCE signalling, including STIM1 and IP3R. Activation of G-protein coupled receptors (GPCRs) signalling that is able to modulate SOCE/ROCE and Ang II induced Ca2+ homeostasis changes in sinoatrial complex being linked to TRPC3. The results provide new evidence that TRPC3 may play a role in sinoatrial and atrial arrhythmias that are caused by GPCRs activation.